The Important Attributes of Local and Imported Apple : A Factor Analysis Application - Rahayu Relawati; Masyhuri Masyhuri; Lestari Rahayu Waluyati; Jangkung Handoyo Mulyo (Agro Ekonomi, 2017)
This study aims to find the important attributes of local and imported apple. A consumer survey was conducted in Java Island representated by four big cities: Malang, Surabaya, Yogyakarta, and Bandung. Three categories of purchasing place at each city are supermarket, fruit stall and traditional market. Accidental sampling was done to choose the samples of consumer. The total respondents interviewed was 240 consumers consisting of 120 for each attribute. The data of apple attributes and purchasing place were analyzed by exploratory factor analysis supported by SPSS software. The result suggests that the important quality attributes of local and imported apples are grouped in each two latent factors namely quality and cultivar. Meanwhile, purchasing place is grouped in one latent factor. All quality attributes of local and imported apples have positive correlation with the apple quality, but there is a different fi nding in which apple flavor of local and imported apples are not the most important attribute that ranked fi rst based on consumer assessment. The factor of apple cultivar always associates with the apple size, both on local and imported apples. Rome Beauty (local apple) and Fuji (imported apple) have greater average size than other cultivars. Thus, these attributes are already attached one another. The factor of purchasing place becomes an important part which accompanies the apple’s quality attributes and is considered by consumers in purchasing apple.